Конструкционные свойства 3d-печатных полимеров - Зайченко, Н. Я. (ХНУРЕ, 2020)
For practical applications, the 3D-printed parts should withstand various amounts of mechanical and environmental stresses during its use. It is important to know the required strengths for each application under various loading conditions, and at the very least, the physical properties of 3D-printed parts should be similar to those manufactured by traditional methods, such as injection molding.
Keywords: 3D печать; полимеры; экструзия; ASTM D638